Examining the Individual Innovativeness and Online Learning Attitudes of Academic Staff in Institutions Providing Sports Training at the Level of Bachelor Degree - Kurudirek, Alparslan Muharrem; Kurudirek, Irfan Muhammet (Asian Journal of Education and Training, 2021)
The purpose of this study was to examine the individual innovativeness and online learning attitudes of academic staff carrying out duty in institutions providing education at the level of bachelor degree in Turkey. The study was conducted online across Turkey via the correlational survey model between September 2020 and November 2020. The population of the study comprised academic staff carrying out duty in faculties of sports sciences in state universities in Turkey. The sample group consisted of 104 academicians who carry out duty in faculties of sports sciences in state universities chosen randomly from the seven regions in Turkey and agreed to participate in the study. The data of the study were collected using the “Personal Information Form”, “Individual Innovativeness Scale (IIS)” and “Online Learning Attitude Scale (OLAS)”. The findings of the study showed that the participants obtained medium mean scores from the general acceptance subscale of online learning attitude scale, lower mean scores from the individual awareness subscale, medium mean scores from the perceived usefulness and application effectiveness subscale, and medium mean scores from the overall online learning attitude scale. On the other hand, the individual innovativeness scale mean scores of the participants were evaluated in the innovator category. As a consequence, it was observed that there was a statistically significant, positive, and high correlation between the online learning attitude and individual innovativeness levels of the participants. Accordingly, as the individual innovativeness levels of the participants increased, their online learning attitude levels increased.